Preparation of the Potential Ocular Inserts by Electrospinning Method to Achieve the Prolong Release Profile of Triamcinolone Acetonide - Shahla Mirzaeei; Kaveh Berenjian; Rasol Khazaei (Tabriz University of Medical Sciences, 2018)
Purpose: The poor bioavailability of drugs in the ocular delivery systems is an important issue and development of delivery systems with prolonged release profile could be in a major importance. This study aims to develop an ocular delivery system using electrospun nanofibers to be a candidate insert for delivery of triamcinolone acetonide. Methods: For this purpose, three different chitosan-based formulations were prepared by electrospinning method, and electrospun nanofibers were compared to a formulation comprising hydrophobic polymers (Eudragit S100 and Zein). The electrospun nanofibers were characterized by SEM and FTIR analyses. The release profile and release kinetic models of all the formulations were also examined. Results: The SEM photographs of electrospun nanofibers revealed that among the four designed formulations, formulation obtained by electrospinning of chitosan and PVP possessed the best quality and the minimum size (120 ±30 nm) , which resulted the most uniform and bead-free nanofibers. This formulation also possessed the prolonged release profile of triamcinolone acetonide and was the only electrospun nanofiber following the zero-order kinetic profile. Due to the small diameter and uniformity of this formulation, the prolonged and well controlled release profile, it could be taken into account as a candidate to overcome the drawbacks of the commonly used ocular delivery systems and be used as ocular insert. Conclusion: This study confirmed the ability of electrospun nanofibers to be used as ocular inserts for delivery of ophthalmic drugs.